Zero inertia density limit for the hyperbolic system of Ericksen–Leslie's liquid crystal flow with a given velocity. (February 2019) - Jiang, Ning; Luo, Yi-Long; Tang, Shaojun
Abstract: Formally when the inertia constant goes to zero, the hyperbolic system of Ericksen–Leslie's liquid crystal flow reduces to the corresponding parabolic system. In this paper, under the assumptions that the initial data are well-prepared and the fluid velocity is given, we justify this limit in the context of classical solutions.